Penanaman Nilai-Nilai Pendidikan Agama Islam Pada Masa Pandemi Covid-19 Di Madrasah Ibtidaiyah - Laili, Faiqotul; Barata, Paga Tri (EDUCARE: Journal of Primary Education, 2021)
The inculcation of Islamic religious values ??is an effort to shape the character of students to achieve a degree as a human being who is in accordance with norms, culture and religion. This research describes the process of internalization and the method of cultivating Islamic religious values ??in an unusual situation, namely in the era of the Covid-19 pandemic. In this study, researchers used a qualitative approach, a type of case study with interview and observation data collection techniques. The results of this study indicate that the implementation of student learning in a pandemic situation is carried out in two ways, namely (1) online and (2) offline. The values ??instilled in students include (a) worship, (b) faith and (c) morals. Meanwhile, the methods used by teachers in the process of inculcating Islamic religious values ??during the pandemic were practice methods, guidance methods, and memorization methods. Keywords: Education, Islamic Religious Values, Covid-19 Penanaman nilai-nilai agama Islam merupakan sebuah upaya dalam membentuk karakter siswa untuk mencapai derajat sebagai manusia yang sesuai norma, budaya serta agama. penelitian ini mendeskripsikan proses internalisasi hingga metode penanaman nilai-nilai agama Islam di situasi yang tidak biasa yakni di era pandemi covid-19. Dalam penelitian ini, peneliti menggunakan pendekatan kualitatif, jenis studi kasus dengan teknik pengumpulan data wawancara dan observasi. Hasil dari penelitian ini menunjukkan bahwa pelaksanaan pembelajaran siswa dalam situasi pandemi dilakukan dengan dua cara yakni (1) daring dan (2) luring. Nilai-nilai yang ditanamkan kepada siswa meliputi (a) ibadah, (b) keimanan dan (c) akhlak. Sedangkan metode-metode yang digunakan guru dalam proses penanaman nilai-nilai agama Islam selama pandemi adalah metode praktik, metode bimbingan, dan metode hafalan. Kata Kunci: Pendidikan, Nilai-nilai Agama Islam, Covid-19